1979
DOI: 10.1002/jss.400100211
|View full text |Cite
|
Sign up to set email alerts
|

Properties of (Mg2+ + Ca2+)‐ATPase of erythrocyte membranes prepared by different procedures: Influence of Mg2+, Ca2+, ATP, and protein activator

Abstract: Erythrocyte membranes prepared by three different procedures showed (Mg2+ + Ca2+)-ATPase activities differing in specific activity and in affinity for Ca2+. The (Mg2+ + Ca2+)-ATPase activity of the three preparations was stimulated to different extents by a Ca2+-dependent protein activator isolated from hemolysates. The Ca2+ affinity of the two most active preparations was decreased as the ATP concentration in the assay medium was increased. Lowering the ATP concentration from 2 mM to 2-200 microM or lowering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…It is relevant to note that our membranes were prepared in EDTA buffers (see Materials and Methods), which, according to the reports of Katz et a1 [23] may lead to membrane preparations devoided of activator protein. On the other hand, Lynch and Cheung [l 11 have demonstrated that erythrocyte membranes can not be completely depleted of calmodulin, even by treatment with such a strong Ca2+ chelator as EGTA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is relevant to note that our membranes were prepared in EDTA buffers (see Materials and Methods), which, according to the reports of Katz et a1 [23] may lead to membrane preparations devoided of activator protein. On the other hand, Lynch and Cheung [l 11 have demonstrated that erythrocyte membranes can not be completely depleted of calmodulin, even by treatment with such a strong Ca2+ chelator as EGTA.…”
Section: Discussionmentioning
confidence: 99%
“…The gel pictures in Figure 1 A, B, and C, when compared with the reports by other authors [21, 221 who used preparation buffers without EDTA, seem to exclude any important qualitative loss of the main protein bands. However, it is important to note that SDS-gel electrophoresis cannot exclude the possibility of a selective extraction of the activator protein by EDTA buffers, as described by other authors [23].…”
Section: + +mentioning
confidence: 97%
“…To assay for the low-affinity ATPase activity, higher concentrations of ATP were used (3 mM). In red cells, Katz et al (1979) found that only the high-affinity enzyme was active at low ATP concentrations (2-20 p M ) , whereas higher concentrations of ATP were needed for the expression of the low-affinity ATPase (above 200 p M ) . When the ATP concentration was more than 1 mM, phosphate was determined by the Lowry-Lopez method (1946), with phosphate standards of 0 to 160 nmolilOO pl.…”
Section: Enzyme Activity Determinationmentioning
confidence: 99%
“…This is comparable to results obtained by a number of other researchers. Katz et al (1979) showed that maximal calmodulin concentrations would 2+ 2+ stimulate Mg -Ca -ATPase 111% in identical membranes, at 0.1 /(M free 2+ Ca . Niggli et al (1979) using EDTA treated membranes, which they 2+ 2+ refer to as hypotonic ghosts, obtained a 301% stimulation of Mg -Ca ATPase activity in the presence of 2/4g calmodulin/mg ghost protein and 2+ 50/vj M Ca .…”
mentioning
confidence: 99%